2019
DOI: 10.1038/s41598-019-42300-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination of eribulin plus AKT inhibitor evokes synergistic cytotoxicity in soft tissue sarcoma cells

Abstract: An activated AKT pathway underlies the pathogenesis of soft tissue sarcoma (STS), with over-expressed phosphorylated AKT (p-AKT) correlating with a poor prognosis in a subset of STS cases. Recently, eribulin, a microtubule dynamics inhibitor, has demonstrated efficacy and is approved in patients with advanced/metastatic liposarcoma and breast cancer. However, mechanisms of eribulin resistance and/or insensitivity remain largely unknown. In this study, we demonstrated that an increased p-AKT level was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…An effect on cell growth in cell lines corresponding to LMS (SK-L-MS1) and FS (HT1080) has also been observed. Similarly, in our study eribulin also produced an inhibitory effect on cell growth in LPS, LMS and FS cell lines [30][31][32].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…An effect on cell growth in cell lines corresponding to LMS (SK-L-MS1) and FS (HT1080) has also been observed. Similarly, in our study eribulin also produced an inhibitory effect on cell growth in LPS, LMS and FS cell lines [30][31][32].…”
Section: Discussionsupporting
confidence: 83%
“…Few combinations have been previously explored in STS cell line models [32,39]. Regarding eribulin combinations, a recent study was published suggesting activity with an AKT inhibitor (MK-2206) in FS and LMS cell lines [31].…”
Section: Discussionmentioning
confidence: 99%
“…Few combinations have been previously explored in STS cell line models [ 32 , 43 ]. Regarding eribulin combinations, a recent study was published suggesting activity with an AKT inhibitor (MK-2206) in FS and LMS cell lines [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…MK-2206, an allosteric AKT inhibitor, binds to the AKT protein in the pleckstrin homology domain resulting in a conformational change of AKT that inhibits the AKT activation by preventing its localization to the plasma membrane (Lindsley et al, 2007). As an anticancer drug, MK-2206 has been proved to be effective both in adult tumors (Djuzenova et al, 2019;Hayasaka et al, 2019) and in a spectrum of pediatric tumors (Gorlick et al, 2012). Phase I studies showed that an oral dose of MK-2206 ranging from 0.25 to 100 mg was well-tolerated (Trucksis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%